Learn more about

Refine search

Results (displaying matches 1-50 of 2754) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
464.a.29696.2 464.a \(y^2 + xy = 4x^5 + 33x^4 + 72x^3 + 16x^2 + x\) $\mathrm{USp}(4)$ 0
672.a.172032.1 672.a \(y^2 + (x^3 + x)y = -x^6 - 16x^4 - 75x^2 + 56\) $G_{3,3}$ 0
800.a.8000.1 800.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^6 + 2x^4 + 4x^3 + 2x^2 - 1\) $G_{3,3}$ 0
990.a.240570.1 990.a \(y^2 + (x^2 + x)y = 3x^5 + 28x^4 + 72x^3 + 28x^2 + 3x\) $G_{3,3}$ 0
1051.b.1051.2 1051.b \(y^2 + xy = x^5 + 8x^4 + 16x^3 + x\) $\mathrm{USp}(4)$ 0
1070.a.2140.1 1070.a \(y^2 + (x^3 + 1)y = x^3 - x\) $\mathrm{USp}(4)$ 1
1122.a.1122.1 1122.a \(y^2 + (x^2 + x)y = x^5 + 7x^4 - 43x^2 + 51x - 17\) $G_{3,3}$ 0
1125.a.151875.1 1125.a \(y^2 + xy = 15x^5 + 50x^4 + 55x^3 + 22x^2 + 3x\) $G_{3,3}$ 0
1147.a.35557.2 1147.a \(y^2 + xy = x^5 + 6x^4 - 32x^2 + x\) $\mathrm{USp}(4)$ 0
1328.a.84992.1 1328.a \(y^2 + (x + 1)y = 4x^5 + 9x^4 + 16x^3 + 13x^2 + 8x + 1\) $\mathrm{USp}(4)$ 0
1386.a.9702.1 1386.a \(y^2 + (x^2 + x)y = x^5 + 20x^4 + 104x^3 + 20x^2 + x\) $G_{3,3}$ 0
1472.a.94208.1 1472.a \(y^2 = 4x^5 - 3x^4 - 4x^3 - x^2 + 7x - 3\) $\mathrm{USp}(4)$ 0
1560.a.199680.1 1560.a \(y^2 + x^2y = 39x^6 - 149x^4 + 189x^2 - 80\) $G_{3,3}$ 0
1575.a.23625.1 1575.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 6x^3 + 2x^2 + 7x - 4\) $\mathrm{USp}(4)$ 1
1575.a.165375.1 1575.a \(y^2 + (x^2 + x + 1)y = -x^5 + 2x^4 + x^2 - 2x\) $\mathrm{USp}(4)$ 1
1680.b.215040.1 1680.b \(y^2 + xy = 4x^5 + 25x^4 + 44x^3 + 15x^2 + x\) $\mathrm{USp}(4)$ 0
1696.a.27136.1 1696.a \(y^2 + (x + 1)y = 4x^5 + 7x^4 + 8x^3 + 3x^2 - 1\) $\mathrm{USp}(4)$ 0
1717.a.1717.1 1717.a \(y^2 + xy = x^5 + 2x^4 + 3x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
1717.a.1717.2 1717.a \(y^2 + xy = x^5 + 9x^4 + 24x^3 + 16x^2 + x\) $\mathrm{USp}(4)$ 0
1734.a.1734.1 1734.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + x^3 + x^2 + x\) $G_{3,3}$ 1
1872.a.1872.1 1872.a \(y^2 + (x^3 + x)y = -x^6 + 8x^4 - 32x^2 + 39\) $G_{3,3}$ 0
1888.a.483328.1 1888.a \(y^2 + x^3y = x^5 - 3x^4 - 16x^3 + x^2 + 64x + 56\) $\mathrm{USp}(4)$ 0
1911.a.5733.1 1911.a \(y^2 + x^2y = x^5 - 4x^4 - 8x^2 - x - 4\) $\mathrm{USp}(4)$ 0
1929.a.52083.1 1929.a \(y^2 + (x^2 + x + 1)y = 9x^5 + 6x^3 + 7x^2 + 2x\) $\mathrm{USp}(4)$ 1
1947.a.578259.1 1947.a \(y^2 + (x^2 + x)y = x^5 + 2x^4 + x^3 - 16x^2 - 8x - 1\) $\mathrm{USp}(4)$ 0
1995.a.341145.1 1995.a \(y^2 + (x^2 + x)y = x^5 + x^4 + 3x^3 - x^2 - 5\) $\mathrm{USp}(4)$ 0
2016.a.4032.1 2016.a \(y^2 + y = -2x^6 - 6x^5 - 10x^4 - 10x^3 - 7x^2 - 3x - 1\) $G_{3,3}$ 0
2058.a.2058.1 2058.a \(y^2 + (x^3 + 1)y = 5x^6 - 4x^5 - 5x^4 + 14x^3 - 5x^2 - 4x + 5\) $N(G_{1,3})$ 0
2080.a.4160.1 2080.a \(y^2 + xy = x^6 + 12x^4 + 48x^2 + 65\) $N(G_{1,3})$ 1
2080.a.4160.2 2080.a \(y^2 + xy = x^6 - 12x^4 + 48x^2 - 65\) $N(G_{1,3})$ 1
2123.a.409739.1 2123.a \(y^2 + xy = x^5 - 5x^4 + 4x^3 - x\) $\mathrm{USp}(4)$ 0
2178.a.13068.1 2178.a \(y^2 + (x^3 + 1)y = -x^6 - x^4 - x^2 - 1\) $G_{3,3}$ 0
2208.a.141312.1 2208.a \(y^2 + (x^3 + x)y = -x^6 + 2x^4 + 29x^2 + 46\) $G_{3,3}$ 0
2223.a.6669.1 2223.a \(y^2 + (x^2 + 1)y = 3x^5 + 3x^4 + 4x^3 - 1\) $\mathrm{USp}(4)$ 0
2250.a.2250.1 2250.a \(y^2 + (x^2 + x)y = x^5 + 2x^4 + 3x^3 + 2x^2 + x\) $G_{3,3}$ 0
2272.a.36352.2 2272.a \(y^2 + (x^3 + x^2)y = 2x^4 + 4x^3 + 7x^2 + 8x + 8\) $\mathrm{USp}(4)$ 0
2272.a.36352.1 2272.a \(y^2 + xy = 4x^5 + 31x^4 + 56x^3 - 16x^2 + x\) $\mathrm{USp}(4)$ 0
2280.a.4560.1 2280.a \(y^2 + (x^3 + x)y = x^6 + 13x^4 + 48x^2 + 57\) $G_{3,3}$ 0
2304.a.13824.2 2304.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^3 + 3x^2 + x + 2\) $\mathrm{USp}(4)$ 1
2304.a.13824.1 2304.a \(y^2 + y = 2x^5 + 3x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2304.b.147456.1 2304.b \(y^2 = -x^6 - 2x^4 - 2x^2 - 1\) $E_1$ 0
2304.c.294912.1 2304.c \(y^2 + x^3y = 4x^4 + 17x^2 + 8\) $G_{3,3}$ 0
2312.c.591872.1 2312.c \(y^2 + xy = -32x^6 - 31x^4 - 10x^2 - 1\) $G_{3,3}$ 0
2345.a.293125.1 2345.a \(y^2 + (x^2 + x + 1)y = -25x^5 - 8x^4 + 6x^2 - 3x\) $\mathrm{USp}(4)$ 1
2352.a.2352.1 2352.a \(y^2 + (x^3 + x)y = -2x^4 + 3x^2 - 3\) $G_{3,3}$ 0
2363.a.2363.1 2363.a \(y^2 + xy = x^5 + 3x^4 + 2x^3 + x\) $\mathrm{USp}(4)$ 0
2371.a.2371.1 2371.a \(y^2 + (x + 1)y = x^5 - 3x^3 + x^2 + 2x - 2\) $\mathrm{USp}(4)$ 0
2405.a.2405.1 2405.a \(y^2 + x^2y = x^5 + 4x^4 - 8x^2 - x + 4\) $\mathrm{USp}(4)$ 1
2432.a.19456.1 2432.a \(y^2 + (x + 1)y = x^6 + 2x^5 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
2457.a.95823.1 2457.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 3x^3 + 6x^2 - 6x + 2\) $\mathrm{USp}(4)$ 1
Next

Download all search results for